Competition between Rhythmic and Linguistic Meaning Revisited: The Effect of Task Demands. Issue 7 (July 2017) - Getz, Laura M.; Wohltjen, Sophie; Kubovy, Michael
This paper revisits the conclusion of our previous work regarding the dominance of meaning in the competition between rhythmic parsing and linguistic parsing. We played five-note rhythm patterns in which each sound is a spoken word of a five-word sentence. We asked listeners to indicate the starting point of the rhythm while disregarding which word would normally be heard as the first word of the sentence. In four studies, we varied task demands by introducing differences in rhythm complexity, rhythm ambiguity, rhythm pairing, and semantic coherence. We found that task complexity affects the dominance of meaning. We therefore amend our previous conclusion: when processing resources are taxed, listeners do not always primarily attend to meaning; instead, they primarily attend to the aspect of the pattern (rhythm or meaning) that is more salient.